Influence of alpine meadow deterioration on soil microbial communities in the Yangtze River source region - Zhang, Wenjuan (Frontiers in Environmental Science, 2023)
Introduction: Although soil microbial populations are a good predictor of soil texture, little is known about how they react to alpine meadow deterioration. Methods: This study utilized Illumina HiSeq sequencing to investigate the effects of alpine meadow degradation on soil microbial communities in the Yangtze River source basin at five different degradation levels [i.e., non–degraded (ND), slightly degraded (LD), moderately degraded (MD), severely degraded (SD), and very severely degraded (VD)]. Results: The results indicated that bacterial and fungal α-diversity were not substantially different (p > 0.05) across the damaged alpine meadows, while β-diversity significantly differed (p < 0.01), indicating a higher variation in the microbial community due to alpine meadow degradation. Proteobacteria reduced considerably (p < 0.05) by 8.75%, 22.99%, and 24.65%, while Acidobacteria increased significantly (p < 0.05) by 41.67%, 85.20%, and 108.67%, in MD, SD, and VD compared with ND, respectively. Ascomycota declined significantly (p < 0.05) in the MD, whereas unclassified phyla rose significantly (p > 0.05) in the VD compared to the ND. The heatmaps of bacterial and fungal communities revealed two clusters: a ND, LD, and MD group and a SD and VD group, suggesting significant changes in soil microorganisms of alpine meadow in the SD and VD. Redundancy analysis (RDA) revealed that soil moisture, soil bulk density, soil organic carbon, total nitrogen, and plant biomass could explain 73.8% and 39.4% of the variance in bacterial and fungal community structure, respectively. Discussion: These findings imply that degradation of the alpine meadow impacts both plant and soil qualities, ultimately leading to changes in soil microbial populations in the Yangtze River’s source region.